Comparison of Inflammatory Mediators in Patients With Atrial Fibrillation Using Warfarin or Rivaroxaban - Martins, Gabriela Lopes; Duarte, Rita Carolina Figueiredo; Vieira, Érica Leandro Marciano; Rocha, Natalia Pessoa; Figueiredo, Estêvão Lanna; Silveira, Francisco Rezende; Caiaffa, José Raymundo Sollero; Lanna, Rodrigo Pinheiro; Carvalho, Maria das Graças; Palotás, András; Ferreira, Cláudia Natália; Reis, Helton José (Frontiers in Cardiovascular Medicine, 2020)
Background: Atrial fibrillation (AF) is the most common arrhythmia associated with high risk of venous thrombo-embolism. Inflammatory mechanisms may be involved in the pathophysiology of AF and in the AF-related thrombogenesis. There is no strong evidence showing whether the use of different oral anticoagulants may present differences in the inflammatory profile of patients with AF. Hence, this study aimed to compare plasma levels of inflammatory markers in individuals with AF treated with either warfarin or rivaroxaban. Methods: A total of 127 subjects were included, divided into three groups: patients with nonvalvular atrial fibrillation (NVAF) using warfarin (n = 42, mean age 71 ± 7); patients with NVAF using rivaroxaban (n = 29, mean age 73 ± 10); and controls in sinus rhythm (n = 56, mean age 72 ± 7). Inflammatory mediators were quantified in plasma samples of these subjects. Results: Individuals of warfarin group presented significantly elevated values of interleukin (IL)-2 (3.49 pg/dL ± 0.51 vs. 2.11 pg/dL ± 0.34 vs. 1.32 pg/dL ± 0.23, p < 0.001), IL-4 (3.45 pg/dL ± 0.72 vs. 2.03 pg/dL ± 0.35 vs. 1.24 pg/dL ± 0.21, p < 0.001) and IL-10 (3.51 pg/dL ± 1.77 vs. 1.85 pg/dL ± 0.50 vs. 1.07 pg/dL ± 0.94, < 0.001), compared to rivaroxaban and control groups. Otherwise, patients treated with rivaroxaban showed elevated levels of monokine induced by interferon-gamma (321.85 pg/dL ± 412.53 vs. 165.12 pg/dL ± 131.85 vs. 162.95 pg/dL ± 191.45, p = 0.012), compared to warfarin and controls, respectively. Conclusions: Levels of anti-inflammatory markers varied between both anticoagulants’ treatment. Further investigation is required to assess the clinical implications of these results and whether rivaroxaban may present an anti-inflammatory effect, as suggested in previous studies.